Impact of the shape of the implantable ports on their efficiency of flow (injection and flushing) - Guiffant G (Dove Medical Press, 2014)
Gérard Guiffant,1 Patrice Flaud,1 Jean Jacques Durussel,1 Jacques Merckx1,2 1Université Paris Diderot, Paris, France; 2University Teaching Hospital Necker-Enfants Malades, Paris, FranceAbstract: Now widely used, totally implantable venous access devices allow mid- and long-term, frequent, repeated, or continuous injection of therapeutic products by vascular, cavitary, or perineural access. The effective flushing of these devices is a key factor that ensures their long-lasting use. We present experimental results and a numerical simulation to demonstrate that the implementation of rounded edge wall cavities improves flushing efficiency. We use the same approaches to suggest that the deposit amount may be reduced by the use of rounded edge wall cavities. Keywords: implantable ports, totally implantable venous access devices, flushing, obstruction, prevention